2008
DOI: 10.1002/mrc.2173
|View full text |Cite
|
Sign up to set email alerts
|

Conformational equilibria of trans ‐3‐X‐cyclohexanols (X = Cl, Br, CH3 and OCH3). A low temperature NMR study and theoretical calculations

Abstract: The integration of 1H and 13C NMR spectra, at - 90 degrees C in CS2/CD2Cl2 (9:1), for the trans-3-chlorocyclohexanol (1), trans-3-bromocyclohexanol (2), and trans-3-methoxycyclohexanol (4) showed that the equatorial-axial (ea) conformer occurs as ca 63, 63, and 69% in the conformational equilibrium, respectively. This corresponds to the following DeltaG(ea-ae) values (from (1)H spectrum): - 0.32 +/- 0.01, - 0.32 +/- 0.04, - 0.48 +/- 0.05 kcal mol(-1); and to (from 13C spectrum): - 0.31 +/- 0.04, - 0.35 +/- 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…A similar axial preference of cyclohexane halo derivatives was observed by Basso and co-workers in cis -2-halocyclohexanols [14], and by de Oliveira and Rittner in trans -3-halocyclohexanols [30]. However, in both studies this preference was not so pronounced as that observed in this work, with a small difference between the populations of the two conformers at equilibrium.…”
Section: Resultssupporting
confidence: 90%
“…A similar axial preference of cyclohexane halo derivatives was observed by Basso and co-workers in cis -2-halocyclohexanols [14], and by de Oliveira and Rittner in trans -3-halocyclohexanols [30]. However, in both studies this preference was not so pronounced as that observed in this work, with a small difference between the populations of the two conformers at equilibrium.…”
Section: Resultssupporting
confidence: 90%
“…Six-membered rings constitute the classical problem in conformational analysis and are closely connected to the birth of modern stereochemistry . The conformational preference is usually rationalized as a delicate compromise among the so-called stereoelectronic effects, which in this context means repulsion between the substituent and the axial hydrogens (1,3-diaxial repulsions) and hyperconjugation. , These effects are intrinsic to each molecule and have been extensively investigated in the gas phase through theoretical calculations. Often, the energy difference between the possible conformers lies below 1 kcal·mol −1 , and it is not rare to find cases in which this conformational energy stays as low as 0.2 kcal·mol −1 . , Attaining such a level of accuracy in solution is one of the greatest challenges for contemporary computational chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Much of what we know about conformational analysis came from the study of substituted cyclohexanes. ,, Cyclohexane rings and analogous heterocyclics appear in the structure of innumerous biologically important molecules and, of course, the role played by these molecules depends on how the substituents interact among themselves and with the solvent media. In this respect, several research groups devoted considerably efforts to dissect the solvent effects on conformational equilibria. ,, …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations